A 5-HT1A receptor promoter polymorphism influences fronto-limbic functional connectivity and depression severity in bipolar disorder. (30th December 2017) - Vai, Benedetta; Riberto, Martina; Ghiglino, Davide; Poletti, Sara; Bollettini, Irene; Lorenzi, Cristina; Colombo, Cristina; Benedetti, Francesco
Abstract: In humans, the G variant of the C(-1019)G 5-HT1A receptor promoter gene polymorphism (rs6295) has been associated with a higher expression of 5-HT1A receptors, increased depression, and worse clinical response. These effects are paralleled by an heightened amygdala (Amy) reactivity to negative emotional stimuli. 5-HT1A receptors are post-synaptically expressed in corticolimbic regions. The aim of this study is to explore if rs6295 could influence Amy functional connectivity (FC) during implicit processing of fearful and angry faces and its relationship with the severity of depressive symptoms in 45 bipolar depressed patients (CC=8, CG=25, GG=12). We observed a significant interactive effect of rs6295 on left Amy–ventrolateral prefrontal cortex (VLPFC) FC during emotional processing. In GG patients, Amy–VLPFC connectivity for emotional stimuli was higher compared to C carriers. Furthermore, rs6295 moderated the relationship between FC and clinical outcome: only in GG subjects the coupling between left Amy and right VLPFC was positively associated with the severity of core depressive symptoms. A deeper comprehension of the naturally occurring genetic variations in the serotonergic system and their effect might provide novel tools in predicting and monitoring disorder outcome in bipolar depression. Highlights: GG patients present an higher Amy–VLPFC connectivity compared to C carriers. rs6295 moderates the relationship between Amy–VLPFC coupling and clinical outcome. Corticolimbic connectivity predicts higher depressive symptomatology in GG patients. Genetic variations in serotonergic system could affect outcome in bipolar disorder.